2021
DOI: 10.14218/jcth.2021.00102
|View full text |Cite
|
Sign up to set email alerts
|

Novel Agents in the Management of Hepatic Encephalopathy: A Review

Abstract: RAVICTI is indicated for use as a nitrogen-binding agent for chronic management of adult and pediatric patients ≥2 years of age with urea cycle disorders (UCDs) that cannot be managed by dietary protein restriction and/or amino acid supplementation alone. RAVICTI must be used with dietary protein restriction and, in some cases, dietary supplements (eg, essential amino acids, arginine, citrulline, protein-free calorie supplements). ( 1) Limitations of Use:  RAVICTI is not indicated for treatment of acute hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 75 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…37 LOLA can also increase urea production by activating the rate limiting enzyme of urea cycle, carbamoyl phosphate synthetase. 38,39 By activation of glutamine synthetase, LOLA also augments glutamine production in perivenous hepatocytes and skeletal muscles. 37,38 Multiple trials confirmed the potential beneficial role of LOLA in HE treatment.…”
Section: Nonabsorbable Antibioticsmentioning
confidence: 99%
See 4 more Smart Citations
“…37 LOLA can also increase urea production by activating the rate limiting enzyme of urea cycle, carbamoyl phosphate synthetase. 38,39 By activation of glutamine synthetase, LOLA also augments glutamine production in perivenous hepatocytes and skeletal muscles. 37,38 Multiple trials confirmed the potential beneficial role of LOLA in HE treatment.…”
Section: Nonabsorbable Antibioticsmentioning
confidence: 99%
“…38,39 By activation of glutamine synthetase, LOLA also augments glutamine production in perivenous hepatocytes and skeletal muscles. 37,38 Multiple trials confirmed the potential beneficial role of LOLA in HE treatment. 40 A metaanalysis including 36 trials with 2377 patients showed that LOLA had beneficial effect on mortality (RR, 0.42; 95% CI, 0.24-0.72) and HE (RR, 0.47; 95% CI, 0.06-3.58) as compared with placebo or no intervention.…”
Section: Nonabsorbable Antibioticsmentioning
confidence: 99%
See 3 more Smart Citations